BROWN BEAR (URSUS ARCTOS) AND GREY WOLF (CANIS LUPUS) BEHAVIOURAL ECOLOGY AND INTERACTIONS WITH LIVESTOCK ACTIVITIES IN FRIULI VENEZIA GIULIA (NORTH-EASTERN ITALY): THE ROLE OF NATURA 2000 AREAS - Marcello Franchini; Lorenzo Frangini; Antonella Stravisi; Stefano Filacorda (2020)
The role of Natura 2000 Areas (N2A) for species conservation has been frequently considered, despite the results obtained are sometimes controversial. The role of such areas is even more important for those most conflictive protected species (i.e., large predators) whose survival is compromised due to conflict with livestock systems. The depletion of apex predators has led to the disruption of ecological processes at a global level. Using data collected from both invasive and non-invasive monitoring methods along with predation data, the present work aimed to assess the role of N2A for both wolves and bears conservation in the north-eastern Italian Alps. The results obtained are species-biased based on the monitoring method used. Hair traps and GPS radiolocations revealed that the majority of bear observations occurred outside N2A. Contrarywise, wolf signs of presence recorded were frequently detected within N2A. The highest number of predation events was recorded outside N2A. Nevertheless, a considerable amount in terms of number of animals killed per event was recorded in lowland areas falling within N2A, where the presence of a stable wolf pack was confirmed. Our work showed poor evidence regarding the relation between N2A and large carnivores’ presence in the north-eastern Italian Alps. However, we caution managers to consider our results as conclusive as the role of such areas, especially in terms of dispersal movements and species conservation, requires further considerations.